Inactivation of Listeria monocytogenes and Salmonella spp. During Cooking of Country Ham and Fate of L. monocytogenes and Staphylococcus aureus During Storage of Country Ham Slices - John B. Luchansky; Kristina Barlow; Brad Webb; Aaron Beczkiewicz; Bryce Merrill; Bryan T. Vinyard; Laura E. Shane; Bradley A. Shoyer; Manuela Osoria; Stephen G. Campano; Anna C.S. Porto-Fett (Journal of Food Protection, 2024)
Thermal inactivation studies were undertaken on Listeria monocytogenes and Salmonella spp. inoculated on the surface of country ham. Hams (average = ca. 3.4 ± 0.5 kg each; average = ca. ≥18% shrinkage) were used as provided by the processor (i.e., “salted hams”), desalted in tap water (i.e., “desalted hams”), or dried for an additional period (i.e., “extra-dried hams”). Hams were surface inoculated (ca. 9.5 log CFU/ham) with a multistrain cocktail of L. monocytogenes or Salmonella spp. and cooked within a bag in a circulating water bath to an internal temperature of 130°F (54.4°C) instantaneous, 145°F (62.8°C) and held for 4 min, 153°F (67.2°C) and held for 34 s, or 160°F (71.1°C) instantaneous. Regardless of ham type, all four time and temperature combinations tested herein delivered a ≥6.7-log reduction of cells of L. monocytogenes or Salmonella spp. Differences in product pH, moisture content, or aw did not have an appreciable impact on the thermal inactivation of L. monocytogenes or Salmonella spp. on country ham. In addition, shelf-life studies were undertaken using slices of “salted” country ham that were surface inoculated (ca. 5.5 log CFU/slice) with a multistrain cocktail of L. monocytogenes or Staphylococcus aureus and then stored at 20°C. Levels of S. aureus increased by ca. ≤1.4 log CFU/slice during storage for 90 days, whereas levels of L. monocytogenes remained relatively unchanged (≤0.2 log CFU/slice increase). Our data validated that cooking parameters elaborated in the U.S. Department of Agriculture’s Food Safety and Inspection Service Cooking Guideline for Meat and Poultry Products (Revised Appendix A) are sufficient to deliver significant reductions (ca. ≥6.8 log CFU/ham) in levels of L. monocytogenes and Salmonella spp. on country ham. In addition, in the event of postprocessing contamination, country ham may support the outgrowth of S. aureus or survival of L. monocytogenes during storage at 20°C for 90 days.